2017
DOI: 10.18632/oncotarget.22573
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and outcome of primary laparoscopic cytoreductive surgery for advanced epithelial ovarian cancer: a comparison to laparotomic surgery in retrospective cohorts

Abstract: ObjectivesTo assess the feasibility and outcome of primary laparoscopic cytoreductive surgery on advanced epithelial ovarian cancer in comparison with conventional open surgery.Materials and MethodsPatients undergoing primary laparoscopic cytoreductive surgery (LCS) from March 2007 to December 2016 were matched to controls treated with laparotomic cytoreduction during the same period. Procedural data and outcomes were analyzed.ResultsThe LCS group (n = 64) and laparotomic group (n = 68) had similar age, BMI, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In highly selected patients, the laparoscopic technique can lead to positive oncological outcomes even for CRS and HIPEC [32]. The postoperative recovery after mini-invasive surgery is faster, with lower pain and incidence of postoperative ileus, a quicker return to solid feeding and systemic chemotherapy, and a significant decrease in postoperative complications [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In highly selected patients, the laparoscopic technique can lead to positive oncological outcomes even for CRS and HIPEC [32]. The postoperative recovery after mini-invasive surgery is faster, with lower pain and incidence of postoperative ileus, a quicker return to solid feeding and systemic chemotherapy, and a significant decrease in postoperative complications [35,36].…”
Section: Discussionmentioning
confidence: 99%
“… 16 Another recent hospital-based study reported lower intraoperative complication rates and considerably lower rates of intraoperative transfusions (9.4% vs 55.9%) for laparoscopy when compared with laparotomy among patients with advanced ovarian cancer. 17 Laparoscopy has been associated in several studies with shorter length of hospital stay when compared with laparotomy. 12 15 , 18 20 Our analyses of in-hospital statistics in Germany included women with ovarian cancer at different stages and showed that ovarian surgeries performed laparoscopically were associated with considerably shorter median hospital stay (4 vs 15 days), lower risk of surgery-related complications and considerably lower risk of in-hospital mortality (0.4% vs 2.9%) in comparison to ovarian surgeries performed by open abdominal surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that minimally invasive techniques have value in evaluation, diagnosis, staging, and management of ovarian cancer [ 78 ]. To date, published studies have been retrospective analyses of small, carefully selected cohorts [ 79 , 80 ]. Both laparoscopic and robotic approaches have been utilized [ 81 ].…”
Section: Minimally Invasive Approaches and Diagnostic Laparoscopymentioning
confidence: 99%